Baragtasan community-campus crossing - Camacho, Marie Gabrielle F.
Baragtasan answers the question of how architecture can redevelop the identity of a place and its community. The project is a connection between Krus na Ligas and the University of the Philippines. It consists of a learning commons, community commons, transit hub, and residences, all of which are joined together by a bridge. The name Baragtasan is a play on the Filipino word balagtasan, which means "dialogue". It is also a combination of the words barangay (community), bagtas (cross), and pamantasan (university). The name signifies a project which will connect and allow for a dialogue between two places. This dialogue will echo on to create the long-sought growth and change.